Efficacy and Safety of Low Molecular Weight Heparin Versus Unfractionated Heparin for Prevention of Venous Thromboembolism in Trauma Patients: A Systematic Review and Meta-analysis. Issue 1 (January 2022) - Tran, Alexandre; Fernando, Shannon M.; Carrier, Marc; Siegal, Deborah M.; Inaba, Kenji; Vogt, Kelly; Engels, Paul T.; English, Shane W.; Kanji, Salmaan; Kyeremanteng, Kwadwo; Lampron, Jacinthe; Kim, Dennis; et al.
Abstract : Purpose: Trauma patients are at high risk of VTE. We summarize the efficacy and safety of LMWH versus UFH for the prevention of VTE in trauma patients. Methods: We searched 6 databases from inception through March 12, 2021. We included randomized controlled trials (RCTs) or observational studies comparing LMWH versus UFH for thromboprophylaxis in adult trauma patients. We pooled effect estimates across RCTs and observational studies separately, using random-effects model and inverse variance weighting. We assessed risk of bias using the Cochrane tool for RCTs and the Risk of Bias in Non-Randomized Studies (ROBINS)-I tool for observational studies and assessed certainty of findings using Grading of Recommendations, Assessment, Development and Evaluations methodology. Results: We included 4 RCTs (879 patients) and 8 observational studies (306, 747 patients). Based on pooled RCT data, compared to UFH, LMWH reduces deep vein thrombosis (RR 0.67, 95% CI 0.50 to 0.88, moderate certainty) and VTE (RR 0.68, 95% CI 0.51 to 0.90, moderate certainty). As compared to UFH, LMWH may reduce pulmonary embolism [adjusted odds ratio from pooled observational studies 0.56 (95% CI 0.50 to 0.62)] and mortality (adjusted odds ratio from pooled observational studies 0.54, 95% CI 0.45 to 0.65), though based on low certainty evidence. There was an uncertain effect on adverse events (RR from pooled RCTs 0.80, 95% CI 0.48 to 1.33, very low certainty) and heparin induced thrombocytopenia [RR from pooled RCTs 0.26 (95% CI 0.03 to 2.38, very low certainty)]. Conclusions: Among adult trauma patients, LMWH is superior to UFH for deep vein thrombosis and VTE prevention and may additionally reduce pulmonary embolism and mortality. The impact on adverse events and heparin induced thrombocytopenia is uncertain. Abstract : Supplemental Digital Content is available in the text